Ginsenoside Rg3: A Review of its Anticancer Mechanisms and Potential Therapeutic Applications - Wu, Lei; Bai, Lin; Dai, Wenshu; Wu, Yaping; Xi, Pengjun; Zhang, Jie; Zheng, Lily (Current Topics in Medicinal Chemistry, 2024)
Background: Traditional Chinese Medicine (TCM) has a long history of treating various diseases and is increasingly being recognized as a complementary therapy for cancer. A promising natural compound extracted from the Chinese herb ginseng is ginsenoside Rg3, which has demonstrated significant anticancer effects. It has been tested in a variety of cancers and tumors and has proven to be effective in suppressing cancer. Objectives: This work covers various aspects of the role of ginsenoside Rg3 in cancer treatment, including its biological functions, key pathways, epigenetics, and potential for combination therapies, all of which have been extensively researched and elucidated. The study aims to provide a reference for future research on ginsenoside Rg3 as an anticancer agent and a support for the potential application of ginsenoside Rg3 in cancer treatment.
Keywords: Ginsenoside Rg3